Efficacy and Safety of 25% Trichloroacetic Acid Peel Versus 30% Salicylic Acid Peel in Mild-to-Moderate Acne Vulgaris: A Comparative Study - Surabhi Dayal (Mattioli1885, 2021)
Background: Both salicylic acid (SA) and trichloroacetic acid (TCA) have proven efficacy with good safety profiles in the treatment of acne vulgaris.